2019
DOI: 10.3390/biom9060205
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Natural Peptide Crotamine from a South American Rattlesnake on Candida auris, an Emergent Multidrug Antifungal Resistant Human Pathogen

Abstract: Invasive Candida infections are an important growing medical concern and treatment options are limited to a few antifungal drug classes, with limited efficacies depending on the infecting organism. In this scenario, invasive infections caused by multiresistant Candida auris are emerging in several places around the world as important healthcare-associated infections. As antimicrobial peptides (AMPs) exert their activities primarily through mechanisms involving membrane disruption, they have a lower chance of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 37 publications
(65 reference statements)
1
13
1
Order By: Relevance
“…The high rate of antifungal resistance of C. auris, and its great ability to form biofilms, creates the need to look for alternative treatments for the infections caused by this yeast. Among the alternatives that have been explored are natural peptides, phenolic compounds, nitric oxide in nanoparticles, as well as the reuse of drugs such as miltefosine and iodoquinol [11][12][13][14][15][16][17]99]. One of the natural peptides with antimicrobial activity is crotamine, a toxin obtained from the rattlesnake's venom [11].…”
Section: Alternative Treatment Strategies In C Aurismentioning
confidence: 99%
See 1 more Smart Citation
“…The high rate of antifungal resistance of C. auris, and its great ability to form biofilms, creates the need to look for alternative treatments for the infections caused by this yeast. Among the alternatives that have been explored are natural peptides, phenolic compounds, nitric oxide in nanoparticles, as well as the reuse of drugs such as miltefosine and iodoquinol [11][12][13][14][15][16][17]99]. One of the natural peptides with antimicrobial activity is crotamine, a toxin obtained from the rattlesnake's venom [11].…”
Section: Alternative Treatment Strategies In C Aurismentioning
confidence: 99%
“…The increase in the prevalence of multidrug-resistant C. auris to different groups of antifungals is a cause for alarm, especially considering that there are few treatment options nowadays. The latter has prompted the search for other therapeutic alternatives such as natural peptides, phenolic compounds, nitric oxide nanoparticles, as well as miltefosine and iodoquinol [11][12][13][14][15][16][17]. The conducted researches are promising, as they show that several of these alternatives can be used alone or in combination with other traditional antifungals, which produces a synergistic effect that potentiates fungal destruction.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that venom peptides from the group of antimicrobial peptides (AMPs) have antibacterial properties [12]. However, it is suggested that AMPs may also exert some antifungal effects such as Pep5Bj peptide from Bothrops jararaca venom (Viperidae family) [26], crotamine from Crotalus durissus terrificus venom (Viperidae family) [27,28] and cathelicidin from the banded krait Bungarus fasciatus venom (Elapidae family) [29]. However, we were unable to identify AMPs in both NPV and NMV (in this study).…”
Section: Npv-and Nmv-mediated Changes In Cell Viability Cell Cycle Amentioning
confidence: 99%
“…Susceptible Candida strains are reference lineages or isolates from patients from São Paulo Hospital (Brazil) and belonging to the collection of the Special Mycology Laboratory, São Paulo Federal University. Multidrug-resistant Candida isolates were previously characterized by our group as resistant to at least two classes of antifungal drugs (Bizerra et al, 2014;Dal Mas et al, 2019). All strains were maintained in glycerol 10% at −80 • C until they were used.…”
Section: Microorganisms Media and Drugsmentioning
confidence: 99%